The Oxford companion to Pakistani history - Jalal, Ayesha (Oxford ; New York : Oxford University Press, 2012)
"Insofar as history is constantly in the process of being reconfigured in the light of new processes and challenges, any Companion to the history of Pakistan cannot but be an ongoing, if not obviously an open-ended enterprise. The historiography of Pakistan has been missing such a comprehensive survey of not only sixty-five years of the country's existence but also of the movement preceding its creation. Pakistan possesses a rich and varied history, considering that it was carved out of the Indian subcontinent, one of the world's oldest civilizations -- hence the prevailing geographical, religious, ethnic, linguistic, and cultural diversities and complexities. 'The Oxford Companion to Pakistani History' has attempted to provide the reader with information on as colourful a spectrum of subjects as possible. This is the first time that all facets of Pakistani history have been covered in one encyclopaedic volume. A wide range of topics have been discussed: from the pre-Partition colonial period to post-Partition movements (religious, political, cultural, etc.), peoples and places, culture, architecture, politics, military, economics, linguistics, archaeology, judiciary, art, theatre, education, foreign relations, government, media, philanthropy, civil society and several others. The Companion differs from other encyclopaedias in the sense that all entries have been written in an analytical, unbiased style by well-known experts in the related field of the topic, paying the keenest attention to factual details. A system of cross-referencing is available through insertion of asterisks within the text linking the entry to another headword that may appear while reading a particular entry. Maps of Pakistan and the Indian subcontinent, along with a Subject Index, are provided at the end of the volume. All these steps have been taken to render the Companion as user-friendly as possible"--Publisher's description, page [4] of dust jacket.
Text in double columns.
Keywords: AYESHA JALAL; Pakistan -- History -- Encyclopedias